2006
DOI: 10.1007/s10705-006-9012-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Long-term Use of Fertilizers and Farmyard Manure on the Adsorption–Desorption Behaviour and Bioavailability of Phosphorus in Soils

Abstract: An understanding of the adsorptiondesorption behaviour of phosphate (P) in soils after three decades of long-term fertilization would be an invaluable supplement to our knowledge of the chemistry of P in soils and would assist in developing P application strategies for successive crops. With this objective and within the framework of a long-term experiment, we collected surface soil samples (0-0.15 m) from agricultural crop land on which a rotation of maize-wheat-cowpea (fodder) crops had been grown for 32 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 17 publications
(20 reference statements)
3
7
0
Order By: Relevance
“…The LVA showed the highest potential sorption capacity for phosphate, with S max values being 2 to 3-fold higher than those of the CR or LV soils. These results were in general agreement with the published literature (Anghinoni et al, 1996;Varinderpal et al, 2006). Varinderpal et al (2006) reported that P adsorption capacity in Indian soils is low, when compared to Brazilian soils, showing a P sorption S max of about 5.5 mmol kg − 1 in soils that had not been fertilized for over 20 years.…”
Section: Phosphorus Sorption-desorptionsupporting
confidence: 92%
“…The LVA showed the highest potential sorption capacity for phosphate, with S max values being 2 to 3-fold higher than those of the CR or LV soils. These results were in general agreement with the published literature (Anghinoni et al, 1996;Varinderpal et al, 2006). Varinderpal et al (2006) reported that P adsorption capacity in Indian soils is low, when compared to Brazilian soils, showing a P sorption S max of about 5.5 mmol kg − 1 in soils that had not been fertilized for over 20 years.…”
Section: Phosphorus Sorption-desorptionsupporting
confidence: 92%
“…Accumulation of organic acids from decomposition of FYM would also compete effectively with orthophosphates for adsorption sites on Fe and Al oxides (Sanyal and Datta 1991) and thus render more P available in soil Table 3 Effect of long-term differential fertilization on Olsen-P and inorganic-P fractions (mg P kg À1 sand) in sand separates of soil solution. Beneficial effects of annual incorporation of FYM (much better even than super optimal application of P fertilizers) in these soils are reported elsewhere (Varinderpal-Singh et al 2006). Interestingly, the differences in Olsen-P content of sand particles in the subsurface layer of these treatments were not so distinct and might be attributed to nearly equivalent organic carbon contents of subsurface soil (Table 2).…”
Section: Resultsmentioning
confidence: 60%
“…Higher adsorption in C 0 N 0 compared to rest of the treatments were ascribed to the presence of more exchange sites because of the 42-year stress on the soil P reserves for meeting crop requirements. The Olsen P content of C 0 N 0 was also lower than that of the fertilized soils, resulted in higher adsorption of P in C 0 N 0 soil [39]. The NPK treatment either alone or in combination with FYM showed lower adsorbed P than the other treatments.…”
Section: Phosphorus Adsorptionmentioning
confidence: 84%
“…It is interesting to note that P adsorption was lowest under the C 1 NPK treatment. This observation could be due to a relatively large amount of residual P in C 1 NPK [39]. The application of FYM played a key role in keeping the applied P in a more available form and, consequently, in reducing P adsorption.…”
Section: Phosphorus Adsorptionmentioning
confidence: 99%